A U-shaped relationship of body mass index on atrial fibrillation recurrence post ablation: A report from the Guangzhou atrial fibrillation ablation registry - Deng, Hai (EBioMedicine, 2018)
BACKGROUND: Obesity or overweight is related to worse outcomes in patients with atrial fibrillation (AF) following catheter ablation (CA). The role of being underweight in relation to recurrent arrhythmias post AF ablation is less certain. We conducted a retrospective study to investigate the association of body mass index (BMI) with arrhythmia outcomes in AF patients undergoing CA. METHODS: In a cohort of 1410 AF patients (mean age 57.2 ± 11.6 years; 68% male) undergoing single CA, the association between BMI and AF ablation outcome was analyzed using BMI as a continuous variable and by four BMI categories (<18.5 kg/m(2), 18.5-24 kg/m(2), 25-29 kg/m(2), and ≥ 30 kg/m(2)). RESULT: We observed a positive association between a cut off value of BMI and risk of AF recurrence post AF ablation. BMI ≥26.36 kg/m(2) was related to more AF recurrence (c-statistic 0.55, 95%CI 0.51–0.58; P < 0.01) with 50% increased risk of AF recurrence (HR 1.50, 95% CI 1.22–1.86; P < 0.01). Recurrence rates in the four BMI categories were 33.3%, 23.2%, 27.2 and 41.8%, respectively (P < 0.01). Kaplan-Meier analysis showed that BMI categories of <18.5 kg/m(2) and ≥ 30 kg/m(2) were all associated with more AF recurrence (P = 0.01). Both underweight (HR 1.85, 95%CI 1.12–3.08; P = 0.02) and obesity (HR 1.78, 95%CI 1.17–2.72; P = 0.01) significantly increased the risk of AF recurrence in a Cox proportional hazard model. CONCLUSION: BMI had good predictive value for AF ablation outcomes with a cut off value of ≥26.36 kg/m(2). Apart from being obese/overweight, being underweight might also be a risk factor for AF recurrence post ablation.